Synthesis of 8-methyl-2-O-methyl-3,5-O-(1-methyl ethylidene)-6,7,8,9-tetradeoxy-D-gulo-6-nonenonic acid (6E)- -lactone - Dao, Phi Thi; Mai Huong, Doan Thi; Phuong, Le Thi; Minh, Chau Van; Cuong, Pham Van (Vietnam Journal of Chemistry, 2015)
Ketide side chain, 8-methyl-2-O-methyl-3,5-O-(1-methylethylidene)-6,7,8,9-tetradeoxy-D-gulo-6-nonenonic acid (6E)-γ-lactone was synthesized starting from the commercial available α-D-glucoheptonic γ-lactone. The synthesis is useful for further synthesis of new and stable bengamide analogues containing an additional methyl group at C-8. The structures of synthetic compounds were determined by spectroscopic analysis, including MS and NMR.